THE INFLUENCE OF CREDIT PROCEDURES AND QUALITY OF SERVICE ON DEBTOR DECISIONS IN CREDIT MAKING (CASE STUDY AT ANUGRAH MEGA MANDIRI COOPERATIVE MEKARSARI BRANCH) - Matdio Siahaan; Damaris Marpaung; Vica Apriyanto (International Journal of Economy, Education and Entrepreneurship, 2021)
This study aims to determine the effect of credit granting procedures and service quality on the debtor's decision to take credit. This research is a descriptive quantitative study with data sources derived from questionnaires and then processed using SPSS version 23. The number of respondents sampled in this study was 80 debtors registered in the Anugrah Mega Mandiri Cooperative Mekarsari Branch. The sampling technique is to use the Purposive Sampling method which is a sampling determination technique with certain considerations or criteria that are used as the basis for sample selection. The data analysis method uses multiple regression analysis methods to analyze the relationship between independent variables, namely the Credit Granting Procedure( and Service Quality( to the dependent variable, namely the Decision to Take Credit (Y). The results showed that partially and simultaneously Credit Provision Procedures and Service Quality significantly and positively influence Credit Decision Making